Genetic Variation in FOXO3 is Associated with Self-Rated Health in a Population-Based Sample of Older Individuals. (5th February 2018) - Zettergren, Anna; Kern, Silke; Rydén, Lina; Östling, Svante; Blennow, Kaj; Zetterberg, Henrik; Falk, Hanna; Skoog, Ingmar
Abstract: Self-rated health (SRH) strongly predicts mortality. Twin studies estimate that genetic factors account for a substantial part of the variability in SRH. Variations in the gene FOXO3 (forkhead box O3), and in genes located at the APOE (apoplipoprotein E) locus, are associated with longevity. This study explores the relationship between SRH and genetic variation related to longevity, in a population-based cohort of older individuals. SRH was assessed among 1, 520 individuals aged 75–87, and five single nucleotide polymorphisms (SNPs), in APOE, TOMM40 (translocase of outer mitochondrial membrane 40 homolog), and FOXO3 were genotyped. Two SNPs (rs10457180 and rs2802292) in FOXO3 were associated with SRH (OR = 2.18 [CI: 1.27–3.76], p = .005 and OR = 1.63 [CI: 1.11–2.40], p = .013), while no associations were found with SNPs in APOE and TOMM40 . Several factors, such as depression, cardiovascular disease (CVD), and diabetes, were related to SRH, but the only factor that had any influence on the association with FOXO3 was CVD. Still, after including CVD as a covariate, the associations between FOXO3 SNPs and SRH remained significant. Our results suggest that FOXO3 is related to SRH in older individuals. This relationship seems to be influenced by CVD, but not by mental and cognitive status.